Analisis Kelayakan Kampung Namicalung Menjadi Desa Wisata Sarung Tenun Legendaris Majalaya - Shinta Larista; Rheinanda Awliya Agista; I Dewa Alit Dwija Putra (Jurnal Syntax Admiration, 2023)
Woven textiles, a vital aspect of Indonesia's cultural heritage, greatly influence the Nusantara archipelago's identity. Majalaya in West Java, known as the "Dollar City," has been a flourishing center for weaving since 1920, notably contributing to the production of woven sarongs, meeting 47% of national demand. In this textile-rich region, Namicalung Village has earned its place in history as a center for sarong weaving, notably recognized for its "poleng" motif. Namicalung's residents aspire to establish the village as a legendary sarong-weaving tourist destination in Majalaya, complying with Provincial Regulation Number 7 of 2020. In pursuing this development, Namicalung must meet specific standards regarding accessibility, amenities, attractions, and institutionalization. A "tourism village" blends attractions, accommodations, and supporting facilities, respecting local traditions and practices. This study aims to conduct a comprehensive feasibility analysis to provide practical guidance for Namicalung's development as a sarong-weaving tourism destination. The research methodology employs an analytical approach to assess various aspects, including tourism potential, infrastructure, economic impacts, and visitor experiences. The outcomes of this research hold significant value in evaluating the overall feasibility of transforming Namicalung Village into a Sarong Weaving Tourism Destination in Majalaya that can assist the local community and stakeholders in taking relevant steps toward the development of an attractive and sustainable tourism destination.